Estimation of the metabolisable energy requirements of feedlot light lambs and comparison with the U. S. National Research Council predictions - Andrés L. Martínez Marín; Manuela Renna; Claudio Forte; Emanuela Valle; Achille Schiavone (Italian Journal of Animal Science)
The aim of the present work was to compare the estimated metabolisable energy requirements (MER) of fattening light lambs raised in feedlot with the U. S. National Research Council (NRC) predictions. Body weight (BW) gain and feed intake were collected from 15 pens (7 lambs/pen) of Manchega male lambs under on-farm conditions over six weeks. The pens were randomly assigned to three dietary treatments (5 pens/treatment) consisting of three concentrates of different composition and barley straw. Feeds were offered for ad libitum consumption throughout the experimental period. Average daily metabolisable energy intake (MEI) was calculated on a weekly basis for each pen from the average daily consumption of concentrate and barley straw and their respective ME contents. Following, the average daily MER was predicted for each pen from the weekly average of both BW and BW gain, according to two models: One including the adjustment of ME for body maintenance (MEm) for the effect of level of MEI on visceral organ tissue energy use as described by NRC (Model 1), and the other excluding such adjustment (Model 2). Model 1 had no mean bias, and exhibited a higher concordance correlation coefficient and a lower underprediction, supporting the need for the upward adjustment of MEm in accordance with MEI to enhance the precision and accuracy of predicted MER. It was concluded that the NRC method was precise and accurate enough to support its application for calculating the MER of feedlot light lambs.